PEDAGOGICAL PRINCIPLES OF APPLYING PHONORHYTHMIC EXERCISES IN THE CORRECTION OF RHINOLALIA (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article analyzes the key scientific and methodological principles of applying phonorhythmic exercises in the process of correcting rhinolalia. Phonorhythmics is examined as an effective speech therapy method aimed at developing the speech apparatus through the harmonious integration of speech, movement, and rhythm. The study scientifically substantiates the necessity of adhering to the principles of individual approach, differentiated approach, systematicity and consistency, as well as integrativity in the organization of phonorhythmic sessions.
Keywords: rhinolalia; phonorhythmics; phonorhythmic exercises